Employees personalization of their workstations in the Office of the University Registrar (OUR) in the University of the Philippines-Diliman - Torres, Jessica T.; Faustino, Johanna Victoria A.; University of ther Philippines. Office of the University Registrar (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study sought to analyze the employees personalization of their workstations in the Office of the University Registrar OUR in the University of the Philippines Diliman, and to examine its effects on their perceived productivity. It was anchored on a framework based on Clemons and Searings research 2004 which states that employees display and arrangement of objects inside their work environment affect their productivity. Participants were selected using a quota sample, non-probability sampling procedure. Qualitative and quantitative data were gathered through survey, interviews, and photo documentation. Out of the current 103 employees in the OUR, 61 answered the four-part survey forms, and 18 were chosen to participate in oneonone interviews. The results of this study indicate that the respondent employees are given freedom to personalize their work environment. When people walk into the offices in the OUR, they see not only the limited colors of the modular furniture and equipment provided by the office, but also the variety of work-related and personal objects displayed and arranged by the employees within their workstations. Rather than complying with the physical setting they came into, they manipulate their areas depending on what makes them comfortable and what they think would help them work better. The findings also indicate that the employees personalize because they have individually assigned workstations, spend long hours at work, and handle sensitive documents. Furthermore, the interviewed employees were ambivalent as to whether or not personalization positively affects their productivity, but all of them mentioned at least one way by which it does. It increases their productivity because it helps them work for longer hours, increase their efficiency, keep important files organized, increase their job satisfaction, increase their organizational commitment, and reduce their stress.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Office decoration -- Philippines; Office layout -- Philippines